Impact of Work Place Ethics on Employee and Organization Productivity - Kaur, Amandeep (Gyan Management Journal, 2019)
In the present globalised and competitive scenario businesses are expected to function within social, ethical, and legally accepted principles in our society in order to satisfy their stakeholders. Ethics in work place has become a very important area for both researchers as well as practitioners. Good ethics is a good business. Bad ethics can derail even the best organizations. The framework of employment relationship necessitates continuous interrogation of the complex issues, which arise from the difference between productivity and employees’ commitment. This paper examines the effects of etiquette and unethical behavior on employee commitment and productivity in India. A descriptive survey research method was adopted for the study using 100 questionnaires, which were administered on Employees in different sectors in India. Secondary data as well as documented evidence were used for the data collection. The sampling procedure was carried out randomly. The data collected were analyzed through Structural Equation Modeling and supported by descriptive statistics. Each item was based on a 5-Point- Likert scale. AMOS 22 was adopted in testing the hypotheses. The data was presented with the use of SPSS while Structural Equation Modeling (SEM) was utilized. The results show that significant relationship exists between ethical standards and organizational productivity, inIndia.